Development of NSDIs in Western Balkan Countries in accordance with INSPIRE. Issue 338 (September 2014) - Cetl, V.; Tóth, K.; Smits, P.
<x content-type="archive" xml:space="preserve">Abstract</x> The INSPIRE Directive requires actions from EU member states and also has direct implications on the countries in the neighbourhood of the EU, regardless of whether they are candidate countries or not. Preconditions for EU membership, to which actually all the countries of Western Balkan (WB) countries aspire is their administrative capacity to incorporate the EU acquis, to fulfil the adopted standards and to execute the assumed obligations. INSPIRE Directive is just one but very important piece of legislation in environmental acquis and is a part of negotiation processes between the European Commission and candidate countries. This paper provides an analysis of the existing status and conditions of National Spatial Data Infrastructures (NSDIs) in WB countries. Results of analysis clearly show that in all countries there are ongoing initiatives on NSDI implementation in line with INSPIRE. The level of implementation between countries however differs but they are all on the right track. In the paper the main existing and future achievements are discussed together with a SWOT analysis. Paper also complements the INSPIRE State of Play Report from 2011, especially with the situation in the countries for which there is no such consistent information available. Finally, some conclusions and recommendations for further developments are given to foster and help WB countries in their efforts to develop NSDIs in accordance with INSPIRE.